ANALYSIS OF THE FORM AND HARMONY OF WIDYA SARASWATI DANCE MOVEMENTS - I Gede Tilem Pastika; I Wayan Sugita (Lekesan: Interdisciplinary Journal of Asia Pacific Arts, 2025)
The Widya Saraswati dance is a mascot dance of UHN I Gusti Bagus Sugriwa Denpasar, created by I Wayan Dibia and I Gede Arya Sugiartha in 2003. This study aims to identify the structural form of the dance and analyze the harmony between its movements, music, and costumes. The analysis is based on Djelantik’s theory of instrumental aesthetics and employs a qualitative research approach. Data were collected through observation, interviews, literature review, and documentation. The findings reveal that the Widya Saraswatidance is a Balinese group dance performed by eight female dancers, representing the characters of Dewi Saraswati, swans, rays, and peacocks, and accompanied by Gong Kebyar music. The choreography, costumes, and makeup remain rooted in the stylistic conventions of traditional Balinese dance. Supporting properties include tunjung flowers, lontar leaves, genitri beads, and a rebab instrument. The harmony between costume and movement is evident in how the costume's form influences character portrayal and movement quality. Similarly, the synchronization between movement and music is achieved through choreography that adheres to the established musical patterns. Although the dance has undergone several structural modifications over time, these changes have often lacked consideration for artistic depth and harmony. This analysis serves as documentation and a means of preserving the dance, ensuring its continued relevance and integrity within Balinese cultural expression.